Strategies for the Preservation, Restoration and Modulation of the Human Milk Microbiota. Implications for Human Milk Banks and Neonatal Intensive Care Units - Fernández, Leónides; Ruiz, Lorena; Jara, Josué; Orgaz, Belén; Rodríguez, Juan M. (Frontiers in Microbiology, 2018)
Studies carried in the last years have revealed that human milk contains a site-specific microbiota and constitutes a source of potentially beneficial bacteria to the infant gut. Once in the infant gut, these bacteria contribute to the assembly of a physiological gut microbiota and may play several functions, contributing to infant metabolism, protection against infections, immunomodulation or neuromodulation. Many preterm neonates are fed with pasteurized donor’s human milk (DHM) or formula and, therefore, are devoid of contact with human milk microbes. As a consequence, new strategies are required to allow the exposition of a higher number of preterm infants to the human milk microbiota early in life. The first strategy would be to promoteand to increase the use of own mother’s milk (OMM) in Neonatal Intensive Care Units (NICUs). Even small quantities of OMM can be very valuable since they would be added to DHM in order to microbiologically “customize” it. When OMM is not available, a better screening of donor women, including routine cytomegalovirus screening of milk, may help to avoid the pasteurization of the milk provided by, at least, a relevant proportion of donors. Finally, when pasteurized DHM or formula are the only feeding option, their supplementation with probiotic bacteria isolated from human milk, such as lactic acid bacteria or bifidobacteria, may be an alternative to try to restore a human milk-like microbiota before feeding the babies. In the future, the design of human milk bacterial consortia (minimal human milk microbiotas), including well characterized strains representative of a healthy human milk microbiota, may be an attractive strategy to provide a complex mix of strains specifically tailored to this target population.